Circulating currents suppression for IPOP nonisolated dc/dc converters based on modified topologies - Xia, Yanghong (2020)
Nonisolated dc/dc converters are widely used in practice because of their low losses and high power density. To accommodate some high-power scenarios and modular applications, these nonisolated converters are usually connected in the input-parallel output-parallel (IPOP) structure. Because there is no galvanic isolation, the ac side and dc side are coupled together, which causes complicated circulating currents in the system. The great circulating currents will endanger the stable and reliable operation of the IPOP nonisolated dc/dc converters system. Focusing on this problem, this paper proposes a novel decentralized circulating currents suppression strategy for IPOP nonisolated dc/dc converters based on the modified topologies, which can still hold the main advantages of nonisolated solutions. First, the complicated circulating currents among the IPOP nonisolated dc/dc converters are analyzed in detail. It is found that various circulating currents exist in the system including the circulating currents within the single converter and the circulating currents among the multiple converters. Then, the limitations of the conventional dc/dc converter topologies are presented and it is proved that these topologies cannot eliminate all the circulating currents. Second, being inspired by the drawbacks of the conventional topologies, the modified topologies with two degrees of freedom modulation are designed. Based on the modified topologies, a corresponding suppression method consisting of two degrees of freedom control is proposed, which can eliminate the different types of circulating currents in a decoupling way. The first degree of freedom control mainly suppresses the circulating currents within the single converter, whereas the droop-based second degree of freedom control mainly suppresses the circulating currents among the multiple converters. Through the proposed solution, the IPOP nonisolated dc/dc converters can operate well with high reliability and scalability. The effectiveness of the proposed solution is validated by the real-time hardware-in-loop tests.